Study of Peak Current Wire-cut EDM on Surface Morphology With Integration CAD/CAM in The Manufacturing of Chain Components - Habiby, M. Nuril Anwar (President University, 2023)
In this increasingly modern era, science and technology (IPTEK) is growing rapidly, one of which is progress in the manufacturing industry sector to produce a product. The machining process that is often used today is Wire Electrical Discharge Machining (WEDM). This machine began to be widely used because it is able to cut workpieces quickly, with good efficiency, and with accurate dimensions. This study aims to study the effect of variations in the use of peak current parameters in the WEDM cutting process by using integration between CAD/CAM software to create programs for manufacturing chain components. Then in the process of cutting the material will be given a variation of peak current treatment to determine the surface morphology. The software used for CAD is Autodesk Inventor Profesional 2015 and the CAM uses the Mastercam X4 application. While the peak current variations use 8, 10, 12 A. The results show that software integration is between Autodesk Inventor Profesional 2015, then the image results are exported to the Mastercam X4 application and can be run on WEDM machines. In addition, the surface morphology images obtained show striking differences with different peak current variations. At high peak currents of 10 and 12A the number of craters produced is larger than the craters at a low peak current of 8A. Besides that, the debris produced on the surface morphology with a higher peak current has a larger size with a greater amount.